ANALISIS NILAI-NILAI RELIGIUS DALAM FILM OMAR & HANA - Widya Dewi Arini; Baso Helmi Baharuddin (Pascasarjana IAIN Sorong, 2022)
The purpose of this research is to find out and describe the religious values in the film Omar & Hana. This study uses library research methods, with the type of research that is library research. Based on the analysis that has been done, it can beconcluded that the religious values in the film Omar & Hana can be categorized into several values, namely: 1) the value of faith, in the episode